Early onset of Friedreich's ataxia in a compound heterozygote. Issue 1 (1st July 2000) - McGovern, Mary Claire; Stewart, Moira; Morrison, Patrick J; Webb, David; Hawkins, Stanley
Abstract : Friedreich's ataxia (FA) is an autosomal recessive condition caused by a GAA trinucleotide repeat expansion in the X25 gene on chromosome 9. We describe an unusual form of "pseudodominant" inheritance to illustrate how a diagnosis of FA in a parent does not preclude the diagnosis in the child.